(untitled) (Jurnal Bahasa, 2021)
This research was conducted to study the co-occurrence of Sabah’s tribal language lexis usage in Corpus "Novel Bahasa Sukuan" (KBNS). This lexis co-occurrence is not arbitrary, on the other hand there is actually a system that binds or controls it. The source of the data was derived from the KNBS data which was developed by the researchers using AntConc 4.2.3w device. The corpus data contains of six novels which narratively crafted based on the background of the indigenous people of Sabah. The novels were the Bagaton and Mariga written by Amil Jaya, whilst the novels entitled Dukanya Abadi, Kukui, Dari Dalam Cermin, and Debur Menerpa were written by Azmah Nordin. A total of 465 lexis of tribal language have been identified and evidently used in conjunction with the KNBS data. Based on these figures, the frequency of lexis mariga in the tribal language is 42. The analysis was carried out using Frame Semantics Theory which was pioneered by Charles Fillmore (1982). The initial results of the study show that the co-occurrence of the lexis mariga existed and were bound with the existence of Sabah’s tribal language. To conclude, the research findings shall be able to explain the function of the mariga lexis and its motivation and potential usage within the context of the Sabah tribal language. Keywords: Lexis, tribal language, Frame Semantic theory, novel